Clinical assessment of anti-viral CD8+ T cell immune monitoring using QuantiFERON-CMV® assay to identify high risk allogeneic hematopoietic stem cell transplant patients with CMV infection complications. - Siok-Keen Tey (Public Library of Science (PLoS), 2013)
The reconstitution of anti-viral cellular immunity following hematopoietic stem cell transplantation (HSCT) is crucial in preventing cytomegalovirus (CMV)-associated complications. Thus immunological monitoring has emerged as an important tool to better target pre-emptive anti-viral therapies. However, traditional laboratory-based assays are too cumbersome and complicated to implement in a clinical setting. Here we conducted a prospective study of a new whole blood assay (referred to as QuantiFERON-CMV®) to determine the clinical utility of measuring CMV-specific CD8+ T-cell responses as a prognostic tool. Forty-one evaluable allogeneic HSCT recipients underwent weekly immunological monitoring from day 21 post-transplant and of these 21 (51.2%) showed CMV reactivation and 29 (70.7%) developed acute graft-versus-host disease (GvHD). Patients with acute GvHD (grade ≥ 2) within 6 weeks of transplant showed delayed reconstitution of CMV-specific T-cell immunity (p = 0.013) and a higher risk of CMV viremia (p = 0.026). The median time to stable CMV-specific immune reconstitution was 59 days and the incidence of CMV reactivation was lower in patients who developed this than those who did not (27% versus 65%; p = 0.031). Furthermore, a failure to reconstitute CMV-specific immunity soon after the onset of CMV viraemia was associated with higher peak viral loads (5685 copies/ml versus 875 copies/ml; p = 0.002). Hence, QuantiFERON-CMV® testing in the week following CMV viremia can be useful in identifying HSCT recipients at risk of complicated reactivation.